The “Bibliotecarias Audaces” exhibition during the 'I Semana DocuFem 2024 - Mujer y Documentación' at the Complutense University of Madrid - Lázaro-Rodríguez, Pedro; Sánchez-Díez, Alicia; Alcázar-Ruiz, Sergio; P.-Elvira, Alejandro; Rodríguez-Romero, Ana-María (Revista de Investigación sobre Bibliotecas, Educación y Sociedad, 2024)
We present all the details about the organization by the DocuFem team of the exhibition “Bibliotecarias audaces: un recorrido de los logros de las profesionales de las bibliotecas a lo largo de la historia”. This exhibition took place at the Faculty of Library Science of the Complutense University of Madrid in March 2024. We explain the origins of the exhibition and its thematic week context (I Semana DocuFem 2024 - Mujer y Documentación) providing technical details of the whole process leading up to the opening day. We share some thoughts and discuss the positive implications for students and teachers of making visible and promoting both female librarians and topics such as gender perspective and equality in the field of Library and Information Science. We also share our upcoming projects regarding the organization of new events on gender perspective and libraries and archives. Finally, we believe that by sharing our experience we provide valuable insights for the organization of events by other people and groups.
Keywords: Female librarians; Gender perspective; Equality; Gender; Women; Libraries; Feminism; Library science; Documentation; DocuFem; Exhibitions; Events